Ready to write : a reading and writing textbook for senior high school - Hernandez, Philippe Jose S.; Esteron, Jerico J.; Watchon, Christhoper B. (Quezon City : Sibs Publishing House, Inc., 2017)
"This book on reading and writing is a response to the need for quality educational materials that are complaint with thrusts of the Senior High School Curriculum." Guided by the theories of constructivism, meaning construction, communicative competence, learner centeredness, project-based learning, standards-based assessment, and Understanding by Design, it provides the students with the needed DepEd-mandated and additional competencies."
Includes bibliography.
English text.
Keywords: Reading; Rhetoric; English language -- Composition and exercises